Điều khiển giá giảm đảm bảo các hệ thống với thông số bất định - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
A general solution is described and applied to a subclass of  linear systems with parameter uncertainties in both the dynamic matrix and the input matrix. An algorithm that ensures the uniqueness and robustness of solution and the stabitity of the closed-loop system is developed.